Side-lobe level reduction in 1D photonic array antennas - Pires De Souza, Bruna Dias; Ferreira, Antonio Elcio; Abbade, Marcelo Luis Francisco; Aldaya, Ivan (Institute of Electrical and Electronics Engineers (IEEE), 2019)
Photonic array antennas have been proposed to improve radiation features and to enable dynamic beam steering and beam forming. In CMOS-compatible photonic array antennas, fabrication constraints, however, limit the minimum separation distance between radiation elements to several wavelengths, which results in the presence of strong side-lobes known as grating lobes. These grating lobes represent a critical impairment that prevents the adoption of these sparse array antennas in applications where crosstalk and security faults must be avoided. In this work, we numerically analyze the side-lobe level (SLL) reduction of 1D sparse antenna arrays under beam steering operation when the radiating elements are arranged non-uniformly (the separation between radiation elements is increased geometrically). The proposed method has a single parameter and, therefore, can be easily optimized. Furthermore, the approach may be extended to higher dimensions. Preliminary results reveal a SLL in the worst-case scenario reduction of approximately 5 dB for a 5-element array with a total length of 6 wavelengths.
Keywords: grating lobes; increasing space; photonic antenna array